The effect of Bilateral Thyroplasty on swallowing for Presbylaryngis - Che Hung Kuo; Hsing Mei Wu; Clint Tanner Allen; Yih Jeng Tsai; Chu Chun Huang; Chia Jung Lee (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Presbylaryngis is defined as age-related structural changes of the vocal folds. Aging results in ossification of the laryngeal skeleton, arthritis of the cricoarytenoid and cricothyroid joints, and structural changes to the superficial layer of the lamina propria that results in true vocal fold bowing [1]. Patients with presbylaryngis often present with symptoms of glottal insufficiency that may include a hoarse-breathy voice, higher than normal pitch and vocal fatigue.